Serum Tetranectin Level and Its Association with Metabolic Parameters in Women with Gestational Diabetes Mellitus: A Case–Control Study - Ozgur Ozdemir; Durmus Onder; Yasin Karadag; Ahmet Ilker Eryilmaz (Healthcare, 2026)
Background/Objectives: Gestational diabetes mellitus (GDM) is a heterogeneous metabolic disorder characterized by impaired glucose regulation and insulin resistance. Tetranectin is a circulating protein implicated in metabolic regulation and diabetes-related dysfunction; however, serum tetranectin levels have not previously been investigated in women with GDM. This study aimed to compare serum tetranectin levels between women with GDM and normoglycemic pregnant controls and to evaluate their associations with metabolic parameters and discriminatory performance for GDM. Methods: This prospective case–control study included 89 pregnant women recruited at the Department of Obstetrics and Gynecology, Antalya Education and Research Hospital, between January 2023 and March 2025, comprising 45 women with GDM and 44 normoglycemic controls. GDM was diagnosed using a 75 g oral glucose tolerance test. Serum tetranectin levels were measured using a commercially available enzyme-linked immunosorbent assay. Clinical, obstetric, metabolic, and laboratory parameters were compared between groups. Correlations between serum tetranectin and metabolic parameters were assessed using Spearman’s correlation analysis. Binary logistic regression was performed to evaluate the independent association between serum tetranectin and GDM. Receiver operating characteristic curve analysis was used to assess discriminatory performance. Results: No statistically significant differences were observed in baseline maternal and obstetric characteristics between the groups. Serum tetranectin levels were significantly higher in women with GDM than in normoglycemic controls (155.42 [147.99–181.36] ng/mL vs. 103.82 [66.89–159.76] ng/mL, p < 0.001). Serum tetranectin was positively correlated with HbA1c (ρ = 0.431, p < 0.001), fasting glucose (ρ = 0.350, p < 0.001), 2 h OGTT glucose (ρ = 0.277, p = 0.009), body weight (ρ = 0.270, p = 0.011), HOMA-IR (ρ = 0.246, p = 0.024), triglyceride levels (ρ = 0.243, p = 0.047), diastolic blood pressure (ρ = 0.241, p = 0.049), and body mass index (ρ = 0.224, p = 0.034). After Bonferroni correction for multiple comparisons, only the correlations with HbA1c and fasting glucose remained statistically significant. In binary logistic regression analysis, each 10 ng/mL increase in serum tetranectin was associated with higher odds of GDM in both crude and adjusted models. After adjustment for maternal age, gestational age at sampling, and body mass index, serum tetranectin remained independently associated with GDM (OR: 1.17, 95% CI: 1.06–1.28, p = 0.001). Receiver operating characteristic analysis demonstrated moderate discriminatory performance, with an AUC of 0.747 (95% CI: 0.635–0.860, p < 0.001). The optimal cut-off value was 124.59 ng/mL, yielding 95.6% sensitivity (95% CI: 84.9–99.5%) and 63.6% specificity (95% CI: 47.8–77.6%). Conclusions: Serum tetranectin levels were significantly elevated in women with GDM and remained independently associated with GDM status after adjustment for maternal age, gestational age at sampling, and body mass index. Serum tetranectin showed associations with several metabolic parameters; however, after multiple-testing correction, only fasting glucose and HbA1c remained significantly correlated with TN. Although its discriminatory performance was moderate, serum tetranectin may represent a biologically plausible circulating biomarker associated with the metabolic environment of GDM. Larger longitudinal studies are needed to validate these findings and clarify the mechanistic role of tetranectin in GDM.